Design of Quasi‐MOF Nanospheres as a Dynamic Electrocatalyst toward Accelerated Sulfur Reduction Reaction for High‐Performance Lithium–Sulfur Batteries. Issue 2 (7th November 2021) - Luo, Dan; Li, Chaojie; Zhang, Yongguang; Ma, Qianyi; Ma, Chuyin; Nie, Yihang; Li, Matthew; Weng, Xuefei; Huang, Rong; Zhao, Yan; Shui, Lingling; Wang, Xin; et al.
Abstract: Lithium–sulfur (Li–S) batteries are considered as one of the most promising next‐generation rechargeable batteries owing to their high energy density and cost‐effectiveness. However, the sluggish kinetics of the sulfur reduction reaction process, which is so far insufficiently explored, still impedes its practical application. Metal–organic frameworks (MOFs) are widely investigated as a sulfur immobilizer, but the interactions and catalytic activity of lithium polysulfides (LiPs) on metal nodes are weak due to the presence of organic ligands. Herein, a strategy to design quasi‐MOF nanospheres, which contain a transition‐state structure between the MOF and the metal oxide via controlled ligand exchange strategy, to serve as sulfur electrocatalyst, is presented. The quasi‐MOF not only inherits the porous structure of the MOF, but also exposes abundant metal nodes to act as active sites, rendering strong LiPs absorbability. The reversible deligandation/ligandation of the quasi‐MOF and its impact on the durability of the catalyst over the course of the electrochemical process is acknowledged, which confers a remarkable catalytic activity. Attributed to these structural advantages, the quasi‐MOF delivers a decent discharge capacity and low capacity‐fading rate over long‐term cycling. This work not only offers insight into the rational design of quasi‐MOF‐based composites but also provides guidance for application in Li–S batteries. Abstract : Quasi‐metal–organic‐framework (quasi‐MOF) nanospheres are developed as a sulfur electrocatalyst, wherein abundant metal nodes that act as active sites are exposed, rendering strong lithium polysulfides absorbability. The dynamic structure evolution over the sulfur reduction reaction can effectively promote catalytic conversion of lithium polysulfides, leading to accelerated reaction kinetics. This quasi‐MOF sulfur composite demonstrates a decent electrochemical performance with prolonged cycle lifespan.